2022
DOI: 10.3390/foods11040573
|View full text |Cite
|
Sign up to set email alerts
|

Aconitic Acid Recovery from Renewable Feedstock and Review of Chemical and Biological Applications

Abstract: Aconitic acid (propene-1,2,3-tricarboxylic acid) is the most prevalent 6-carbon organic acid that accumulates in sugarcane and sweet sorghum. As a top value-added chemical, aconitic acid may function as a chemical precursor or intermediate for high-value downstream industrial and biological applications. These downstream applications include use as a bio-based plasticizer, cross-linker, and the formation of valuable and multi-functional polyesters that have also been used in tissue engineering. Aconitic acid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 108 publications
0
13
0
Order By: Relevance
“…Aconitic acid plays various biological roles within cells as an intermediate in the tricarboxylic acid cycle. It confers unique survival advantages to some plants as an antifeedant, antifungal, and means of storing fixed pools of carbon [ 41 ]. Aconitic acid has also been reported as an inhibitor of fermentation, an anti-inflammatory, and a possible nematicide [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aconitic acid plays various biological roles within cells as an intermediate in the tricarboxylic acid cycle. It confers unique survival advantages to some plants as an antifeedant, antifungal, and means of storing fixed pools of carbon [ 41 ]. Aconitic acid has also been reported as an inhibitor of fermentation, an anti-inflammatory, and a possible nematicide [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…It confers unique survival advantages to some plants as an antifeedant, antifungal, and means of storing fixed pools of carbon [ 41 ]. Aconitic acid has also been reported as an inhibitor of fermentation, an anti-inflammatory, and a possible nematicide [ 41 ]. The time-kill assay with 6.25 g·ml −1 of dehydroabietic acid showed that it killed Staphylococcus epidermidis (American Type Culture Collection 14,990) bacteria within 24 h [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The 4-aminobutyric acid usually exhibits potential functions in carbon metabolism, plant development and defense, nitrogen storage, and pH regulation [ 47 ]. Aconitic acid plays various biological functions in plant cells as an inflammatory inhibitor or an antifeedant [ 48 ]. E. gansuensis might improve the competitiveness of host plants by mediating the accumulation of 4-aminobutyric acid as well as aconitic acid under normal growth conditions.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable interest in using aconitic acid as a chemical precursor or reactant with its three reactive carboxylic acid groups. It is especially attractive, since it can be inexpensively sourced from renewable agricultural byproducts such as sugarcane molasses and sweet sorghum syrup to produce bio-based products and chemicals with various properties that we recently reviewed [ 2 ]. For instance, aconitic acid has been used in the production of polyesters, hyper-branched polyesters, polymers, and as a chemical crosslinker, plasticizer, and grafting agent [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its numerous chemical applications, aconitic acid has several biological roles and functions that were recently summarized by Bruni and Klasson [ 2 ], and it has many bioactive functions in specific plants and microorganisms, including its impact on nematodes [ 8 , 9 , 10 ]. Clarke and Shepherd [ 8 ] reported that in a study of 444 inorganic and organic compounds, trans -aconitic acid was one of 45 compounds that stimulated the eggs of the potato cyst nematode Heterodera rostochiensis (now named Globodera rostochiensis ) to hatch at 3 mM (0.500 mg/mL) but it was not among the strongest stimulants.…”
Section: Introductionmentioning
confidence: 99%